Fatigue performance of hybrid fibre metal laminate structure - Ng, Lin Feng; Dhar Malingam, Sivakumar; Zakaria, Kamarul Ariffin; Selamat, Mohd Zulkefli (Praise Worthy Prize, 2017)
Increasing the knowledge about the fatigue performance of thermoplastic-based fibre metal laminate is crucial for further extending their applications. In this study, the density and tension-tension fatigue performances of laminate structures with different hybrid layups are investigated. The fibre metal laminate structure is formed by bonding the composite laminate to annealed aluminium 5052 by using polypropylene adhesive through the hot press moulding compression method. The fatigue test was conducted at force controlled constant amplitude loading in accordance with ASTM E466. The results show that hybrid composite laminates layups of kenaf/glass/kenaf reinforced metal laminate improve the tensile and fatigue strength by 9%, compared to composite laminates layups of kenaf/kenaf/kenaf fibre reinforced metal laminate. Meanwhile, the hybrid composite laminates layups of glass/kenaf/glass reinforced metal laminate show an increase in tensile strength and fatigue strength by 30% and 4% respectively. In terms of fatigue sensitivity, a hybrid laminate system with kenaf/glass/kenaf composite construction had better performance than other layups.